Evaluasi Program Pengentasan Kemiskinan Berbasis Pemberdayaan Masyarakat: Studi Kasus Pada Program Gerdu-Taskin di Kabupaten Malang - Murdiansyah, Isnan (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2014)
The biggest issue of national economic development is the high rate of poverty. Several efforts and solutions in the form of financial help program had been conducted by the government to overcome poverty problems, especially through an integrated act to overcome poverty program (Gerdu-Taskin).This program aimed to decrease poor-people through self-independency using human developmental approach, enterprises, and environment; on 2007, which was developed to be the link of social economic security (Japes). Malang, one of district in East Java, became one of district who got financial help program. Therefore, this study aimed to examine the role of Gerdu-Taskin in powering up the poor-people and identifying each motivating and demotivating factors for Gerdu-Taskin to increase social welfare in the District of Malang. This study was taken place at Pandanrejo village, the subdistrict of Pagak, the District of Malang. It used explorative study by applying descriptive qualitative method. The result of study investigated that; first, the Gerdu-Taskin through the Financial Controlling Unit effectively played important role in powering up and improving the people-self-independency, especially in the study area at the south of Malang. Second, the implementation of Gerdu-Taskin program through â€œAnggrekâ€ Financial Controlling Unit is as one of study area that effectively played important role in improving the rural-area institutional development. Third, the Gerdu-Taskin played important role in improving the social welfare in the District of Malang. The positive correlation between the both is able to be a role model to overcome poverty issues at other areas. Fourth, there are some problems appeared on the process of implementation of Gerdu-Taskin in Malang were the limited funds, corruption, the troubled-funds, the strong intervention of rural-area apparatus, the low support from both rural-area institution and the rural-area government, and the coordination among the manager programs in the district/ city had not yet gone well. Fifth, there were some advantages in Gerdu-Taskin program which was conducted by UPK in study area of Malang were the circulating of funds went well, the competency of staff management was professional, skillful, especially the people around the area.